The labor market in Belgium, 2000-2016 - Vincent Bodart; Muriel Dejemeppe; Bruno Van der Linden (IZA World of Labor, 2018)
Might the Belgian labor market be included in the gallery of “Belgian surrealism”? At first sight, Belgium with its 11 million inhabitants has withstood the Great Recession and the euro area debt crisis relatively well, quickly getting back on track toward growth and employment, apparently without rising earnings inequality. But if one digs a little deeper, Belgium appears to be a strongly segmented labor market, first and foremost in an astounding north–south regional (linguistic) dimension. This extreme heterogeneity, along with several demographic challenges, should serve as a warning for the future.
Keywords: J21; J24; J31; 330; labor market; segmentation; earnings; Belgium